Analisis Strategi Pengendalian Persediaan Bahan Makanan Pada Hotel Four Points by Sheraton Ungasan Bali - Mertayasa, I Gusti Agung Kadek Rai; Indraswarawati, Sang Ayu Putu Arie; Putra, I Made Endra Lesmana (Hita Akuntansi dan Keuangan, 2025)
Hotels are accommodation providers that areeexpected to survive and develop their business by optimising their operational activities. Currently, Four Points Ungasan Hotel is facing problems in its purchasing function because some procedures have not been carried out properly, which has a significant impact on the high cost of purchases while affecting its food costs. Thus, food inventory control needs to be analysed. The purposeeof this studyywas to determine the analysis of food inventory strategies at Four Points by Sheraton Ungasan Hotel Bali. This study uses a qualitativeemethod with dataavalidity testing using source triangulation to compareethe resultssof interviews with the results of observations. The results showed that there were deviations in the procurement of food ingredients in purchasing, receiving and storing in practice did not carry out the SOP designed by the company. which has a significant impact on the high cost of purchases while affecting its food cost in 2022.